Ethical and Moral Aspects of School Education: The situation in the Czech Republic - Jiří Mareš (Charles University, 2020)
Abstract: This review study focuses on ethical and moral aspects of school education in the Czech Republic after 1989, when change occurred not only in the political regime but also in all spheres of social life, including education. The study is based on publications by Czech authors and is structured into six parts. The fi rst part describes the broader context of the chosen issue: it describes the basic philosophical concepts of ethics and morality and reminds offi cial materials (starting with the International Teachers' Charter, through materials created by the Ministry of Education, to the school rules of individual schools). The second part provides an overview of publications dealing with the ethical and moral education of children and adolescents from the perspective of various scientific disciplines: philosophy, theology, sociology, and psychology. The third part presents the organizational form of ethical and moral education at Czech basic and secondary schools. In terms of its content and conception, ethics education as a subject taught in Czech schools is based on the concept of prosocial education (Roche-Olivar, 1992), adapted by the Slovak author Ladislav Lencz (1995). The fourth part is devoted to a specifi c genre, review studies which provide information about Czech and foreign research studies, and evaluates them. The fifth and most extensive part reports on selected Czech empirical studies that deal with the ethical and moral aspects of education. It presents research on cyberbullying addressed to both pupils and teachers and mobbing and bossing in schools, examines the course and outcomes of teaching ethical topics, researches the power relations between teachers and their pupils, and examines the tendencies for teachers and pupils to be manipulated at school, cheating by pupils at school, and pupils helping one another. The sixth and last part of the study describes assessment tools with the help of which the ethical and moral aspects of school education are determined. The study concludes that one-off transversal research studies predominate in the studies, while longitudinal research studies are not conducted at all; mainstream research focuses on real-life research and no intervention studies are undertaken; researchers' attention is focused mainly on negative ethical and moral situations, while research into positive phenomena is neglected. Keywords: ethics education, moral education, school, teachers, pupils, research, Czech Republic